Comparison of anthropometry to DXA: a new prediction equation for men - Ball, S.D; Altena, T.S; Swan, P.D (European journal of clinical nutrition, 2004)
Objective: This study compared three professionally recommended anthropometric body composition prediction equations for men to dual energy X-ray absorptiometry (DXA), and then developed an updated equation, DXA Criterion (DC) from DXA. Design: Cross-sectional. Setting: Exercise Physiology Lab. University of Missouri-Columbia, USA. Subjects: A total of 160 men aged 18-62 y old. Interventions: Percent body fat (%BF) by anthropometry was compared to DXA on the same day. Results: Although %BF was significantly correlated (r=0.923-0.942) (P<0.01) with DXA for all three equations, each equation underestimated %BF (range=3.1-3.3%) (P<0.01) compared to DXA. The following DC equation for men was created: %BF=0.465+0.180(sigma7SF)-0.0002406(sigma7SF)2+0.06619(age); (sigma7SF=sum of chest, midaxillary, triceps, subscapular, abdomen, suprailiac, thigh; age=years). The predicted residual sum of squares (PRESS) R2 was high (0.90) and the PRESS standard error of estimates was excellent (2.2% at the mean) for the DC equation when applied to our sample of 160 men. Conclusions: The currently recommended anthropometric equations for men underestimate %BF compared to DXA. The DC equation yields a more accurate estimation of %BF in men aged 18-62 y old. The results from this study support the need for the current %BF standards and norms for men to be adjusted upward.